Ontology of doomed existence: foundations of existential liberation therapy - Yamauchi, Cyntia Regina de Oliveira (Seven Editora, 2023)
The present analysis essay had as its central objective to trace a dialogue with the first chapter of the work Doomed Existences, by Professor Dr. Gustavo Alvarenga Oliveira Santos, and under this construct to discuss the Existential Liberation Therapy (TEL). The therapeutic praxis organized by Alvarenga is based on the philosophical decolonial clipping, thus talking with the Latin American decolonial schools of thought, which connect and distance themselves from the phenomenological-existential tradition of European. At first, we will seek to situate the reader on what comes to be the doomed existence, based on the decolonial criticism of the phenomenological-existential ontology of European tradition. Later, we will approach the praxis of The Existential Therapy of Libertação(TEL), aiming to deepen the concepts: of Che, Ñandé, Oré, and Kuaitá as well as think about the therapeutic relationship, because it requires, on the part of the therapist, versatility, flexibility, and sensitivity to deal with community emergencies. To finalize, we link the story of Alex, revealed in the book Doomed Existences, with the Foundations of Existential Liberation Therapy, to propose this decolonial turn, as it is traditionally known. DOI: https://doi.org/10.56238/devopinterscie-041